Two Borderline Works: The Miniature Classical Friezes by John Henning - Rambaldi, Simone (Actual Problems of Theory and History of Art, 2020)
The theme of the article is two plaster replicas of the miniaturized reproductions of the Parthenon and Bassae friezes made in London by the Scottish sculptor and carver John Henning in the first decades of the 19th century. The reliefs were recently revealed during a new exhibition of the Plaster Cast Gallery, belonging to the Department of Cultures and Societies of the University of Palermo in Italy. Henning based himself on the original marbles transferred to the British capital and, in the case of the Athenian frieze, onthe drawings of the missing parts. Through a long job, his reproductions in miniature were carved in reverse into slate slabs from which plaster casts were easily obtained and finally sold. A lucrative trade of bootlegged copies arose, but Henning gained nothing by that business. The duplicates spread in great numbers not only in plaster casts galleries, but also inside dwelling houses, as an ornament for walls and chimneys in living rooms. These artifacts, although they have seldom captured the attention of the archaeologists, are of particular interest. The casts performed a two fold function: on one hand, they were useful for study; on the other hand,they were used as furnishing elements. The small casts by Henning, furthermore, were suitable for the taste of the time. Despite their astonishing fidelity to the originals, the sharp and chiseled contours of the carved figures emanate more neoclassical than classical aura, especially in the parts of the Parthenon frieze not directly known by the author. In that, we understand how these artifacts, though they are reliable reproductions of sculptures dating from the culminating point of Greek art, are also two typical “industrial” products of the 19th century. Henning’s artwork seems to appear as a real “borderline work”. It stands between the ancient and the modern, art and handicraft, public and private, study and pleasure.